Analisis Resepsi Mahasiswa terhadap Brand Image Shopee pada Kampanye 10.10 Shopee di Instagram - Dina Fitriana Subekti; Johantan Alfando; Dony Kristian; Harry Isra Muhammad (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze audience reception of Shopee’s brand image in the 10.10 campaign on the Instagram account @shopee_id. The research employed a descriptive qualitative method using Stuart Hall’s reception analysis through the encoding–decoding modelwhich classifies audience interpretation into three positions: dominant-hegemonic, negotiated, and oppositional. Brand image was analyzed based on Keller and Swaminathan’s indicators: strength, favorability, and uniqueness of brand associations. Data were collected through in-depth interviews, observation, and documentation involving seven Communication Studies students from Mulawarman University, class of 2022, selected through purposive sampling. The findings reveal diverse audience receptions toward Shopee’s brand image. Two informants occupied the dominant-hegemonic position, accepting Shopee’s image as an affordable, practical, and trustworthy e-commerce platform. Four informants were categorized in the negotiated position, accepting the campaign message while remaining critical of promotional claims perceived as inconsistent with their shopping experiences. One informant occupied the oppositional position, rejecting the constructed image as not fully reflecting reality. The 10.10 campaign successfully strengthened the strength of brand associations, while favorability and uniqueness were perceived differently across audiences. These findings indicate that brand image formation is influenced by audience interpretation and contribute to audience reception studies, with practical implications for designing more relevant and credible digital marketing campaigns.